PENGEMBANGAN APLIKASI ANDROID WEBLOG SIFAT KOLIGATIF LARUTAN BERBASIS CHEMO-EDUTAINMENT - Siti Sarwani; Elvi Yenti (Journal of Chemistry Education and Integration, 2023)
Indonesia is facing the industrial era 4.0, where all systems are digitally connected, thus demanding the world of education to constantly adapt technological developments to efforts to improve the quality of education, especially in the use of learning media. This study aims to produce a learning media design in the form of an Android Weblog application based on Chemo-edutainment and to determine the feasibility level and students' responses to the media. This research is a type of Research and Development (R&D) development research. This research uses the Brog and Gall development model, which is limited to the 5th stage, namely data collection, planning, initial product development, initial trials and revisions. The initial trial was conducted at SMAN 5 Tapung on two chemistry teachers and 10 class XII MIA students. The data obtained were then analyzed using qualitative and quantitative descriptive analysis techniques. The Chemo-edutainment-based Weblog Android application on material colligative properties of solutions that have been tested is very valid with a percentage of 93% from media experts, 75% valid from material experts, and practicality tests by teachers and students obtain a percentage of 88.6% with efficient criteria. However, this research still has some shortcomings so it is expected that in the future an effectiveness test will be carried out to determine the effectiveness of the media.Keywords : Android Aplication, Weblog, Chemo-Edutainment, Colligative Solution Properties